3-(3-Cyanophenyl)-N-phenyloxirane-2-carboxamide - Kang, Tai-Ran (International Union of Crystallography, 2010)
In the title compound, C(16)H(12)N(2)O(2), both terminal benzene rings are located at the same side of the central epoxide ring, showing a cis conformation. The epoxide ring makes dihedral angles of 76.59 (10) and 62.40 (11)° with the phenyl and cyanophenyl rings, respectively. Intermolecular N—H⋯O and weak C—H⋯O hydrogen bonding is present in the crystal structure.